2016
DOI: 10.1038/onc.2016.135
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine prostate cancer (NEPCa) increased the neighboring PCa chemoresistance via altering the PTHrP/p38/Hsp27/androgen receptor (AR)/p21 signals

Abstract: Prostatic neuroendocrine cells (NE) are an integral part of prostate cancer (PCa) that are associated with PCa progression. As the current androgen-deprivation therapy (ADT) with anti-androgens may promote the neuroendocrine PCa (NEPCa) development, and few therapies can effectively suppress NEPCa, understanding the impact of NEPCa on PCa progression may help us to develop better therapies to battle PCa. Here we found NEPCa cells could increase the docetaxel-resistance of their neighboring PCa cells. Mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 66 publications
0
26
0
1
Order By: Relevance
“…Further investigations into how these changes facilitate NEPC development could be a promising area of research, especially given its contribution to metastasis and the hypoxic response . It has also been suggested that in prostatic tumors containing a mixture of NE and adenocarcinoma cells, certain paracrine factors secreted by NE cells could facilitate the growth and aggressiveness of neighboring adenocarcinoma cells . Whether the increased secretion of lactic acid from NE cells could function in an analogous paracrine fashion to enhance PCa aggressiveness would be an intriguing area for further study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further investigations into how these changes facilitate NEPC development could be a promising area of research, especially given its contribution to metastasis and the hypoxic response . It has also been suggested that in prostatic tumors containing a mixture of NE and adenocarcinoma cells, certain paracrine factors secreted by NE cells could facilitate the growth and aggressiveness of neighboring adenocarcinoma cells . Whether the increased secretion of lactic acid from NE cells could function in an analogous paracrine fashion to enhance PCa aggressiveness would be an intriguing area for further study.…”
Section: Resultsmentioning
confidence: 99%
“…13,14 It has also been suggested that in prostatic tumors containing a mixture of NE and adenocarcinoma cells, certain paracrine factors secreted by NE cells could facilitate the growth and aggressiveness of neighboring adenocarcinoma cells. 15,16 Whether the increased secretion of lactic acid from NE cells could function in an analogous paracrine fashion to enhance PCa aggressiveness would be an intriguing area for further study. Finally, inhibition of glucose metabolism via CD44 has also been reported to sensitize NEPC cells to platinum-based chemotherapy.…”
Section: Inhibition Of Mct4 Expression In Nepc Cells Reduces Cell Pmentioning
confidence: 99%
“…Although the functions of these NE peptides remain to be fully elucidated, some factors such as bombesin, neurotensin, serotonin, calcitonin and thyroid‐stimulating hormone may have potential mitogenic effects . In addition, the conditional medium of NEPC cells could promote chemoresistance in surrounding AdPC cells by modulating the PTHrP/p38/Hsp27/AR/p21 axis . Concurrently, benign and tumour‐associated NE cells were reported to have increased expressions of survival factors including survivin and Bcl‐2 .…”
Section: Neuroendocrine Differentiationmentioning
confidence: 99%
“…Previous studies have reported that miR218 served as a tumor suppressor in high-grade localized PCa and in metastatic cells, 18 and that miR218 could target CDH2 and ZEB2, thereby preventing EMT in lung cancer. 29,30 We performed MS2-RIP and Ago2-RIP to confirm that lncAPP binds miR218 directly, and by overexpressing/downregulating lncAPP expression levels to conduct Ago2-RIP, we observed declining/increasing enrichment of ZEB2 and CDH2 mRNA to the Ago2-based RISC, which might suggest that lncAPP could compete with ZEB2 and CDH2 transcripts for binding miR218. We analyzed the mRNA expression levels of lncAPP, CDH2 and ZEB2 in RNA-seq data, and conducted immunohistochemistry of CDH2/ZEB2 and in situ hybridization of lncAPP in PCa tissues.…”
Section: Discussionmentioning
confidence: 95%